PENGARUH EARNING PERSHARE DAN DEBT TO EQUITY RATIO TERHADAP RETURN SAHAM DENGAN KEBIJAKAN DEVIDEN SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN YANG TERDAFTAR DALAM INDEKS LQ45 DI BURSA EFEK INDONESIA (BEI) TAHUN 2017-2021 - Ghina, Kaisul; Wahyuni, Ika; Subaida, Ida (Fakultas Ekonomi dan Bisnis, 2023)
Financial management is all activities related to financial management decisions and financial assets. The main objective of financial management is to obtain maximum profit through owned financial resources. The purpose of this study is to analyze and test the effect of the Effect of Earning Per Share and Debt To Equity Ratio on Stock Returns with Dividend Policy as Intervening Variables in Companies Listed in the Index LQ45 on the Indonesia Stock Exchange (IDX) 2017-2021. The target population in this study were companies listed on the LQ45 index on the Indonesia Stock Exchange (IDX) for 2017-2021, totaling 45 companies, which were then reduced based on the criteria to become 7 companies. Data analysis and hypothesis testing in this study used the Structural Equation Model - Partial Least Square (PLS-SEM). The results of the direct effect hypothesis test using the Smart PLS 3.0 application, show that Earning Pershare has a positive but not significant effect on Dividend Policy, Debt To Equity Ratio has a positive but not significant effect on Dividend Policy, Earning Pershare has a significant positive effect on Stock Returns, Debt To Equity Ratio has a positive but not significant effect on stock returns, dividend policy has a positive but not significant effect on stock returns. The results of the indirect effect hypothesis show that the Earning Pershare variable has a positive but not significant effect on Stock Return through Dividend Policy, Debt To Equity Ratio on Stock Return through Dividend Policy has a positive but not significant effect.